Phase formation, microstructure and luminescence properties of calcium–magnesium–aluminosilicate based glass-ceramics with Eu3+ doping. (July 2015) - Senanon, W.; Tipakontitikul, R.; Niyompan, A.
Abstract: The glass-ceramics from CaO–MgO–Al2 O3 –SiO2 system with the Eu 3+ doping were prepared by a melt-quenching technique following by a controlled crystallization step employing the heat treatment process. The selected treatment temperatures were guided by the DTA measurement. The obtained glass-ceramic samples were characterized by the XRD, SEM and fluorescence spectroscopy. The results of XRD revealed that Mg2 (Si2 O6 ) and Diopside (CaMg(SiO3 )2 ) presented as two major embedded crystalline phases. This observation was consistent with the result of SEM which showed the presence of well-shaped crystallites with size in nano-scale. With the increasing of the heat treatment temperature, the approximated crystallite volume fraction increased gradually and induced the change of phase type. Fluorescence technique was applied to characterize the role of Eu 3+ ions after entering into the glass-ceramics. By recording the excitation and emission spectra at room temperature, the main emission peak of the samples located at a wavelength of 613 nm after subjecting to 394 nm excitations. This indicated that the obtained glass-ceramics can be applied as a red phosphor.